HTS-Compatible CometChip Enables Genetic Screening for Modulators of Apoptosis and DNA Double-Strand Break Repair. (September 2020) - Tay, Ian J.; Park, James J. H.; Price, Anna L.; Engelward, Bevin P.; Floyd, Scott R.
Dysfunction of apoptosis and DNA damage response pathways often drive cancer, and so a better understanding of these pathways can contribute to new cancer therapeutic strategies. Diverse discovery approaches have identified many apoptosis regulators, DNA damage response, and DNA damage repair proteins; however, many of these approaches rely on indirect detection of DNA damage. Here, we describe a novel discovery platform based on the comet assay that leverages previous technical advances in assay precision by incorporating high-throughput robotics. The high-throughput screening (HTS) CometChip is the first high-throughput-compatible assay that can directly detect physical damage in DNA. We focused on DNA double-strand breaks (DSBs) and utilized our HTS CometChip technology to perform a first-of-its-kind screen using an shRNA library targeting 2564 cancer-relevant genes. Conditions of the assay enable detection of DNA fragmentation from both exogenous (ionizing radiation) and endogenous (apoptosis) sources. Using this approach, we identified LATS2 as a novel DNA repair factor as well as a modulator of apoptosis. We conclude that the HTS CometChip is an effective assay for HTS to identify modulators of physical DNA damage and repair.